Enactment of compassionate leadership by nursing and midwifery managers: results from an international online survey - Papadopoulos, Irena; Wright, Steve; Lazzarino, Runa; Koulouglioti, Christina; Aagard, Magdeline; Akman, Ozlem; Alpers, Lise-Merete; Apostolara, Paraskevi; Araneda, Julieta; Biglete-Pangilinan, Sylvia; Eldar-Regev, Orit; González Gil, María Teresa; et al. (My University, 2021)
Aim To explore the views of an international sample of nursing and midwifery managers concerning attributes that they associate with compassionate management. Method A cross-sectional online survey. Using a snowballing sampling method, 1217 responses were collected from nursing and midwifery managers in 17 countries. A total of complete 933 responses to a question related to which actions and behaviours indicated that a manager was exercising compassionate leadership were analysed for this paper. First, content analysis of the responses was conducted, and second, a relative distribution of the identified themes for the overall sample and for each participating country was calculated. Results Six main themes were identified describing the attributes of a compassionate leader: (1) Virtuous support, (2) Communication, (3) Personal virtues of the manager, (4) Participatory communication, (5) Growth/ flourishing/ nurturing and (6) Team cohesion. The first three themes mentioned above collectively accounted for 63% of the responses, and can therefore be considered to be the most important characteristics of compassionate management behaviour. Conclusion The key indicators of compassionate management in nursing and midwifery which were identified emphasise approachability, active and sensitive listening, sympathetic responses to staff members’ difficulties (especially concerning child and other caring responsibilities), active support of and advocacy for the staff team and active problem solving and conflict resolution. While there were differences between the countries’ views on compassionate healthcare management, some themes were widely represented among different countries’ responses, which suggest key indicators of compassionate management that apply across cultures.
Keywords: Nursing; Midwifery; Management; leadership; Compassion